Training Simulator for Acquiring Operational Skill to Operate Overhead Traveling Crane while Suppressing Load Sway - Yoshiyuki Noda; Ryuki Hoshi; Akihiro Kaneshige (Shock and Vibration)
The present study addressed an advanced system that was designed to teach the skills needed to operate an electric overhead traveling crane. In the operation of an overhead traveling crane, to ensure the safe and efficient transport of a load, an operator must be able to suppress the sway of that load. However, considerable training is needed to master this skill. Furthermore, the beginners may cause accidents by operating the crane incorrectly. Therefore, in the present study, we devised a training system in which an operator can safely and efficiently master the operation of an electric overhead traveling crane while suppressing the load sway. In this approach, the operational conditions in which the load sway is suppressed can be derived theoretically. The operational conditions are displayed by the crane simulator as visual instructions in a virtual working environment. The efficacy of the proposed skill training approach with the crane simulator was verified through experiments whereby novices used the crane simulator to perform the task of transporting a load while suppressing load sway.